Research Progress on Malignant Transformation Mechanism of Precancerous Diseases of Breast Cancer. Issue 5 (June 2019) - Xia, Dong; Ran, Rui; Bobo, Meng; Yan, Fang; Yanfang, Pan; Hong, Li; Xiaoping, Ying
Abstract: Breast cancer occurs in the epithelial tissue of breast, which is one of the most common female cancers in the world. In recent years, with the improvement of people's living standards, the incidence of breast cancer is also growing rapidly, so the prevention of breast cancer is very significant. At present, the etiology and pathogenesis of breast cancer are still unknown. Precancerous diseases are benign breast lesions with potential canceration, which may develop into breast cancer if they have not cured for a long time. This paper summarizes the latest research progress on the mechanism for malignant transformation of breast precancerous diseases in recent years, hoping to provide theoretical reference for basic research and early clinical diagnosis of breast cancer.